2021
DOI: 10.1088/1757-899x/1062/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Student Attendance System Using Fingerprint Biometrics for Kolej Universiti Poly-Tech Mara

Abstract: Recording students’ attendance has been a major concern at Kolej Universiti Poly-Tech Mara. However, monitoring the attendance manually is a cumbersome issue to lecturers as students tend to manipulate the attendance by signing each other’s attendance. It has been found that fingerprint biometrics is capable to monitor the attendance systematically and efficiently. The aim of this study is to verify the students’ attendance using fingerprint biometrics. Evolutionary prototyping model were used to develop the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One of the most used formulas to achieve excellent academic performance is the attendance to classes by students, so to validate their presence in the classroom, it is necessary to control the integrity of the attendance record of students through an appropriate procedure that checks and manages the attendance data [1], which currently, is manual in many schools, such as universities, which leads to errors such as miscalculating the number of attendances, wasted time in collecting attendance data, false attendances, filling out the attendance list is prone to student fraud [2], among others, are recurrent problems when the attendance control process is carried out manually, this not only affects the final decision-making of an institution, as one study found a significant relationship between attendance and students' academic performance [3]; monitoring and managing attendance is essential, therefore, to assist staff interacting with the attendance monitoring process, it needs to be improved [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most used formulas to achieve excellent academic performance is the attendance to classes by students, so to validate their presence in the classroom, it is necessary to control the integrity of the attendance record of students through an appropriate procedure that checks and manages the attendance data [1], which currently, is manual in many schools, such as universities, which leads to errors such as miscalculating the number of attendances, wasted time in collecting attendance data, false attendances, filling out the attendance list is prone to student fraud [2], among others, are recurrent problems when the attendance control process is carried out manually, this not only affects the final decision-making of an institution, as one study found a significant relationship between attendance and students' academic performance [3]; monitoring and managing attendance is essential, therefore, to assist staff interacting with the attendance monitoring process, it needs to be improved [4].…”
Section: Introductionmentioning
confidence: 99%